Memoryless H ∞ controller design for switched non-linear systems with mixed time-varying delays - Phat, Vu N. (International journal of control, 2009)
This article deals with the H ∞ control problem for a class of switched non-linear systems with mixed time-varying delays. The novel features here are that the system in consideration is non-linear perturbation with discrete and distributed delays, the time-varying delay is also involved in the observation output, and the controllers to be designed satisfy some exponential stability constraints on the closed-loop poles. By using Lyapunov-Razumikhin functional approach, new sufficient conditions for the H ∞ control with exponential stability constraint are derived in terms of the solution of Riccati-type equations. The approach allows for simultaneous computation of the two bounds that characterise the stability rate of the solution.